PEMANFAATAN PUPUK ORGANIK CAIR LIMBAH TAHU DAN AIR KELAPA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L.) - Marti Susilawati; Adiwirman Adiwirman; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The study aims to determine the effect of tofu waste POC, coconut water as a natural growth regulator and their interaction as well as to get a POC concentration of coconut water waste out and deliver the highest on the growth and production of green beans.This study was conducted at experimental field of Faculty of Agriculture, University of Riau, Pekanbaru. The study was conducted over three months, from November 2016 - January 2017.Research conducted experimentally in the field using a factorial RAK, which consists of two factors. The first factor is the concentration of POC waste out (T), namely: T0: 0%, T1: 25%, T2: 50%, T3: 75%. The second factor is the concentration of coconut water (K), namely: K0: 0%,      K1: 25%, K2: 50%, K3: 75%. Of the two factors were obtained by 16 combination treatment and each repeated 3 times so that there are 48 experimental units. Observations on this research that plant height (cm), number of primary branches (branch), age appears interest (HST), number of pods/plants (peas), the percentage of peas pithy (%), weight of pods/plant (g), weight of the pods/plot (g), dry weight of seed/plant (g), the dry weight of seeds/m2 (g) dry weight of 100 seeds (g). Results were analyzed using analysis of variance, if significantly different from continuing use HSD test level of 5%. The results showed that administration of tofu waste POC concentration 75% increase seed dry weight/m2. Provision of coconut water concentration of 50% increased plant height and age appearsmemepercepat interest, whereas the concentration of coconut water, giving 75% increase in dry weight of 100 seeds. Giving out waste POC concentration of 25% and 50% coconut water concentration gives the number of pods/plant, pod weight/plant, pod weight/dry weight of 100 plots and the highest seed. Giving out waste POC concentration showing 75% dry weight of seed/m2 highest green bean plant that is 9.58 g/m2, equivalent to 59.87 kg/ha. Keywords : Growth and production, green beans, POC waste out, coconut water.